2009
DOI: 10.1016/j.jpsychores.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits in women with multiple sclerosis: Discrepancy in patient/partner report and disease course

Abstract: Objective-Patients diagnosed with multiple sclerosis (MS) are believed to undergo personality changes, which could have implications for how they perceive themselves and are perceived by others. We endeavored to examine the extent to which patients' self-perceptions are congruent with how they are perceived by significant others across five trait domains as demarcated by the well known Five-Factor Model (FFM).Methods-The NEO Five-Factor Inventory (NEOFFI) (Costa and McCrae, 1992) was administered to women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
0
15
1
2
Order By: Relevance
“…In addition, Benedict et al (2009) suggest that the Big Five perspective is a good theory for investigating disease-related personality changes in patients with MS. Men probably cope more negatively with MS due to their impaired coping and appraisals in such situation may increase their fatigue, their depression levels, and also may increase changes in their personality. MS may influence fatigue and depression levels because of their limited social resources, the increment of psychosocial stressors, and the application of an emotional coping style.…”
Section: Coping Styles In Men With Msmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Benedict et al (2009) suggest that the Big Five perspective is a good theory for investigating disease-related personality changes in patients with MS. Men probably cope more negatively with MS due to their impaired coping and appraisals in such situation may increase their fatigue, their depression levels, and also may increase changes in their personality. MS may influence fatigue and depression levels because of their limited social resources, the increment of psychosocial stressors, and the application of an emotional coping style.…”
Section: Coping Styles In Men With Msmentioning
confidence: 99%
“…Pakenham (1999) indicated that Big Five perspective of personality might help to understand personality changes in patients with MS. The Big Five model suggests that the greater the use of severe emotions and emotion-focused coping style in patients with MS, the more increases the risk of mental disorders and disease-related changes in personality (Benedict et al, 2009;Pakenham, 1999).…”
Section: Personality Traits and Msmentioning
confidence: 99%
“…İrritabilite ve apati ile karakterize kişilik değişiklikleri MS hastalarının %20-40'ında görülmektedir (3). MS hastalarında kişilik özelliklerinin değerlendirildiği sınırlı sayıda çalışma bildirilmiştir (4,5,6,7).…”
Section: Introductionunclassified
“…The reliable judgment of others’ personality characteristics is important for guiding social interactions in everyday settings (Funder, 1995; 2003; McAdams & Pals, 2006) and in research contexts where self-report data are unavailable (Useda et al, 2007) or of dubious reliability (Benedict et al, 2009; Duchek, Balota, Storandt, & Larsen, 2007; Siegler, Dawson, & Welsh, 1994). In clinical practice, informant ratings of personality are useful as a complement to self-report (Costa & Piedmont, 2003; Ganellen, 2007; Klein, 2003; Vazire & Mehl, 2008), but only if the ratings are reliable and discrepancies between self- and informant-report can be probed.…”
mentioning
confidence: 99%